Analisis Kepuasan Anggota Sebagai Pelanggan pada Unit Niaga Barang Koperasi Pegawai Pemerintah Provinsi Jawa Barat - Lely Savitri Dewi; Wanda Wanida; Muhammad Haris Fadhillah (LPPM Universitas Koperasi Indonesia, 2026)
This study aims to analyze the level of member satisfaction as customers at the Goods Business Unit of the West Java Provincial Government Employee Cooperative (KP3Jabar). The background of this study is driven by the phenomenon of member shopping switching behavior to non-cooperative retail, which is triggered by issues regarding price, location, product variety, service, and retail layout. This research applies a quantitative approach with a descriptive method using the Importance-Performance Analysis (IPA) approach. Primary data were gathered through structured questionnaires distributed to 32 respondents selected via non-probability sampling with a purposive sampling method. The results of the descriptive analysis and conformity level show that the majority of marketing mix indicators have met customer expectations with a value above 90%. Based on the Cartesian diagram mapping, the results indicate that: (1) the location indicator (X4.2) is positioned in Quadrant I (Top Priority), meaning it has a high level of importance but suboptimal performance; (2) the price competitiveness indicator (X1.3) is located in Quadrant IV (Possibly Overkill), meaning its performance is rated well but not highly crucial for the members. As a tactical recommendation, the cooperative is advised to optimize online media promotion and consider providing delivery services to overcome the constraints of the business unit's physical location